Social policy and the environment - Huby, Meg. (Buckingham ; Philadelphia : Open University Press, 1998)
Water. Food. Housing. Warmth and domestic energy. Mobility and travel. Recreation and leisure. Summary and discussion.
Keywords: Environmental aspects; Social policy; Social policy -- Environmental aspects; Environmental responsibility; Sustainable development; Human ecology; Great Britain -- Social policy -- Environmental aspects; Great Britain -- Social policy